1992
DOI: 10.1116/1.577763
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of indium nitride by low energy modulated indium and nitrogen ion beams

Abstract: Indium nitride deposition on Si(100) using modulated In+ and N+2 has been carried out in a mass-separated low energy ion beam system. In+ and N+2 were generated in a Colutron ion source loaded with pure indium and fed with nitrogen, and were focused into a Wien filter. The mass analyzer was switched manually or by a computer for modulating the selection of In+ and N+2. After passing through the Wien filter, the selected ion beam was focused to the target chamber and was decelerated by a five-element decelerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…34,35 This observed difference in stoichiometry from surface and bulk of the films have been explained by preferential sputtering of N atoms by Ar + ions used to sputter and depth profile the film of interest. Despite the fact that Ar + ion etching of InN does not provide information about stoichiometry from the bulk of the film due to limitation of preferential etching, it is a suitable method to estimate impurity concentration within the bulk of the film.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…34,35 This observed difference in stoichiometry from surface and bulk of the films have been explained by preferential sputtering of N atoms by Ar + ions used to sputter and depth profile the film of interest. Despite the fact that Ar + ion etching of InN does not provide information about stoichiometry from the bulk of the film due to limitation of preferential etching, it is a suitable method to estimate impurity concentration within the bulk of the film.…”
Section: Resultsmentioning
confidence: 99%
“…Bello et al showed that the most probable formations in InN other than indium-nitride are oxynitrides. 35 Any form of N-O bonding will appear in the spectra at higher binding energy with respect to the main peak (396.4 eV), i.e., the shoulder peak can be attributed to the presence of In-O bond. 36,37 XPS-measured valence band spectrum of HCPA-ALD grown sample was obtained in order to extract information about electronic structure of the InN sample (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The SiN bond strength is strong and the SiNx species was formed during the surface photolysis of HN 3 on Si. 1 2 The SiNx was also found in the InN film deposition process using In+ and N 2 + ion beams, 11 where an atomic ratio of less than 0.4 was reported for N:ln as alluded to above. In the present study, we found that the In:N ratio is -0.9, which becomes 1.1 if the 398.3 eV component is excluded.…”
Section: Amentioning
confidence: 99%
“…3 Other methods, such as reactive rf-sputtering and ion plating have also been tried in order to produce the InN films. 7 -10 Using low energy In+ and N 2 + ion beams, Bello et al 11 were able to grow InN on a Si(100) surface; however, the resulting InN showed an N:ln atomic ratio of <0.4. The growing of InN films on Si substrates is more difficult probably because of lattice mismatch and silicon nitride formation.…”
Section: Introduction Rlmentioning
confidence: 99%